2017
DOI: 10.1039/c7fo00910k
|View full text |Cite
|
Sign up to set email alerts
|

The impact of extrusion on the nutritional composition, dietary fiber and in vitro digestibility of gluten-free snacks based on rice, pea and carob flour blends

Abstract: Consumers and the food industry are demanding healthier products. Expanded snacks with a high nutritional value were developed from different rice, pea and carob flour blends. The proximate composition, starch (total and resistant), amylose and amylopectin, dietary fiber (soluble and insoluble) contents, and the in vitro protein digestibility of different rice-legume formulations, were evaluated before and after the extrusion process. Compared with the corresponding non-extruded blends (control), the extrusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 40 publications
8
72
2
2
Order By: Relevance
“…After extrusion, due to high shear and high temperatures, starch granules are damaged and starch is leaching, partly or completely gelatinizing and melting. It is becoming susceptible to physical damage and hydrolysis, as well as more accessible to enzymes that can rapidly hydrolyze it to glucose (Arribas et al, ; Sopade, ). Consequently, the RS content in extruded samples dropped to between 0.17% (in the control sample) and 0.40% (in the sample with 15% of cocoa husks).…”
Section: Resultsmentioning
confidence: 99%
“…After extrusion, due to high shear and high temperatures, starch granules are damaged and starch is leaching, partly or completely gelatinizing and melting. It is becoming susceptible to physical damage and hydrolysis, as well as more accessible to enzymes that can rapidly hydrolyze it to glucose (Arribas et al, ; Sopade, ). Consequently, the RS content in extruded samples dropped to between 0.17% (in the control sample) and 0.40% (in the sample with 15% of cocoa husks).…”
Section: Resultsmentioning
confidence: 99%
“…Flours with different ratios of rice, beans and carob fruit were prepared in order to obtain six formulations. The different proportions of each flour were selected according to previous studies (Arribas et al, 2017;Varela et al, 2007) in order to obtain extrudates with adequate technical characteristics (expansion index and bulk density) (data not shown). The mixtures included calcium carbonate and salt to improve the texturisation and flavour, respectively (Table 1).…”
Section: Samples Preparationmentioning
confidence: 99%
“…In previous studies (Arribas et al, 2017;Arribas, Cabellos, Cuadrado, Guillamón, & Pedrosa, 2019), it has been reported that the extrusion of rice, pea and carob fruit blends enable the making of nutritious and phytochemical-rich food products that are suitable for establishing a healthy lifestyle. However, it has not been evaluated for the potential bioactivities, such as cytotoxicity, anti-inflammatory and antimicrobial.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an extract of pea albumins led to an anti-inflammatory effect at the colon level in mice, accompanied by a modulation in the composition of the intestinal microbiota, [30][31] and dark kidney beans or cranberry bean supplements suppressed colonic inflammation and reduced the severity of DSS-induced colitis in mice. [32][33] As explained in the accompanying paper, 34 new highly palatable extruded mixes of legumes plus cereals similar to a snack food have been produced 35 and incorporated in limited amounts into normocaloric or obesogenic diets for rats. Our purpose was to evaluate the effects of dietary incorporation of this new food ingredient on lipids (accompanying paper 34 ) and intestinal microbiota composition (current paper).…”
Section: Introductionmentioning
confidence: 99%